The Relationship between Surface Temperature and Land Use using Multi-Temporal Remote Sensing Imagery in Muang Udon Thani District - Suwanlee, Savittri Ratanopad; Somard, Jaturong; Chainprakhon, Kantaphit; Nuanhong, Ninrat; Ratanatip, Sontaya (Burapha Science Journal, 2026)
This study aimed at investigating the relationship among surface temperature, land use and surface temperature distribution for 22 year period with Landsat satellite imagery 5, 7 and 8 between 1997 – 2019 and analyzing patterns of spatial distribution of surface temperature using spatial autocorrelation together with land use. The study of land use obtained data from satellite of 2019 using random forest (RF). The data on land use in 2019 together with average surface temperature acquired from thermal infrared band for 22 year period was analyzed to identify patterns of spatial distribution of surface temperature for global indicator using spatial autocorrelation (Moran’ I), and for local indicator using Local G-Statistics and Local Indication of Association (LISA) with the size of grid of 300 x 300 meters. The results found that in classifying land use RF yielded more accuracy (87%), most of the area was agricultural and urban community area. The analysis of surface temperature changes and patterns of surface temperature distribution for 22 year period indicated that annual average surface temperature increased in average by 6.6˚C. The patterns of distribution of global spatial autocorrelation were found to be clustered highest in urban and bare land. The results of the analysis of the relationship between average surface and building area yielded R2 equal 0.9641 and this indicated the highly degree of correlation of these two sets of data.